If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 5)(x + -1)(x + 3) = 0 Reorder the terms: (5 + 2x)(x + -1)(x + 3) = 0 Reorder the terms: (5 + 2x)(-1 + x)(x + 3) = 0 Reorder the terms: (5 + 2x)(-1 + x)(3 + x) = 0 Multiply (5 + 2x) * (-1 + x) (5(-1 + x) + 2x * (-1 + x))(3 + x) = 0 ((-1 * 5 + x * 5) + 2x * (-1 + x))(3 + x) = 0 ((-5 + 5x) + 2x * (-1 + x))(3 + x) = 0 (-5 + 5x + (-1 * 2x + x * 2x))(3 + x) = 0 (-5 + 5x + (-2x + 2x2))(3 + x) = 0 Combine like terms: 5x + -2x = 3x (-5 + 3x + 2x2)(3 + x) = 0 Multiply (-5 + 3x + 2x2) * (3 + x) (-5(3 + x) + 3x * (3 + x) + 2x2 * (3 + x)) = 0 ((3 * -5 + x * -5) + 3x * (3 + x) + 2x2 * (3 + x)) = 0 ((-15 + -5x) + 3x * (3 + x) + 2x2 * (3 + x)) = 0 (-15 + -5x + (3 * 3x + x * 3x) + 2x2 * (3 + x)) = 0 (-15 + -5x + (9x + 3x2) + 2x2 * (3 + x)) = 0 (-15 + -5x + 9x + 3x2 + (3 * 2x2 + x * 2x2)) = 0 (-15 + -5x + 9x + 3x2 + (6x2 + 2x3)) = 0 Combine like terms: -5x + 9x = 4x (-15 + 4x + 3x2 + 6x2 + 2x3) = 0 Combine like terms: 3x2 + 6x2 = 9x2 (-15 + 4x + 9x2 + 2x3) = 0 Solving -15 + 4x + 9x2 + 2x3 = 0 Solving for variable 'x'. The solution to this equation could not be determined.
| 9x-4=10x-11 | | -6x=a-70 | | X-9=x(3)-8 | | 60x=46.6597 | | 2(90)-9=180-y | | 10(4x+2)=20(6) | | x*60=59.409 | | Y=180-9 | | 90=2(90)-18 | | 40(x-20)=40(3) | | 90=180-y | | 7x^5-33x^4+3x+52=0 | | 4x^2-3=1x | | 16a-263a=b | | 90-y=(2y)-18 | | x^7+5x^3+x-4=0 | | 16t-263t=h | | x^5-6x^3-16x=0 | | 7x^6+15x^2+1=0 | | 14x^2-5/7x | | 180-y=(3y)+56 | | log21x=2/3 | | 180-y=(3y)+44 | | x*60=72.1414 | | 27 = w8 | | 5(-4x-7)-5=-100 | | 54=9k | | s=10(4) | | 10x+32=72 | | x*0.06=72.1414 | | X+5+67=90 | | 2x-29+3x-21=180 |